2010
DOI: 10.1177/1741143210383895
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Management and Leadership within Colleges and Schools Somewhat Differently: A Practice-based, Actor-Network Theory Perspective

Abstract: This article examines the significance of materiality for management and leadership in education using resources provided by actor—network theory (ANT). Espousing the idea that human interactions are mediated by material objects and that these objects participate in the production of practices, ANT affords thinking management and leadership in a somewhat different way. Drawing on empirical data collected over the course of examining management and leadership in vocational education institutions in Australia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Indeed, ANT seems to strike a chord among those scholars that are interested in eliciting the "messiness" of academic experience, especially as it contrasts with the "official story", embedded for example in workload allocation systems (Malcolm and Zukas 2009). ANT-informed studies are no longer a rarity within the field of education, and their focus areas span from literacy (Edwards, Ivanic, and Mannion 2009) to educational policy (Decuypere, Simons, and Masschelein 2011) and academic management (Mulcahy and Perillo 2011). The study described in this article may be situated at the intersection of management-oriented educational research and pedagogy-oriented research, as it deals with issues related to the daily practices of academic staff in a Higher Education setting.…”
Section: Theoretical Backdropmentioning
confidence: 99%
“…Indeed, ANT seems to strike a chord among those scholars that are interested in eliciting the "messiness" of academic experience, especially as it contrasts with the "official story", embedded for example in workload allocation systems (Malcolm and Zukas 2009). ANT-informed studies are no longer a rarity within the field of education, and their focus areas span from literacy (Edwards, Ivanic, and Mannion 2009) to educational policy (Decuypere, Simons, and Masschelein 2011) and academic management (Mulcahy and Perillo 2011). The study described in this article may be situated at the intersection of management-oriented educational research and pedagogy-oriented research, as it deals with issues related to the daily practices of academic staff in a Higher Education setting.…”
Section: Theoretical Backdropmentioning
confidence: 99%
“…This implies that lecturers who are accessible and provide teaching and learning materials and deliver high quality lectures to students positively influenced them towards achieving their academic goals. Mulcahy and Perillo (2011) found that action based management perspective impacted positively on educational management and improved staff and students' participation. By action based management perspective, the study means the proactive nature of an institution's policy on teaching and learning.…”
Section: Lecturers' Leadership Practices and Students' Participation mentioning
confidence: 98%
“…The debate however, is not solely concerned with structure/agency dichotomies but also concerned with networks. Mulcahy and Perillo (2010) remind that agency is distributed across various entities. Vocational teachers are influenced by the networks where vocational knowledge and skills are enacted into being, where they network with the tools, ideas and mores of the vocational area and it is to these particular networks that we now turn.…”
Section: Agency Of Vocational Teachersmentioning
confidence: 99%